Australian athlete support personnel lived experience of anti-doping. Issue 2 (May 2015) - Mazanov, Jason; Hemphill, Dennis; Connor, James; Quirk, Frances; Backhouse, Susan H.
Highlights Support personnel lived experience of anti-doping diverges from policy. Support personnel need greater assistance from anti-doping organisations. Support personnel report normalisation of doping early in athletic careers.